Women's monasticism and medieval society : nunneries in France and England, 890-1215 - Venarde, Bruce L., 1962- (Ithaca : Cornell University Press, 1997)
"In this innovative and engaging work, Bruce L. Venarde uncovers a largely unknown story of women's religious lives and puts female monasticism in the mainstream of medieval ecclesiastical history. Venarde deftly interweaves narrative and statistical data to describe in broad historical context the multiplication of French and English nunneries during the central Middle Ages."--Jacket.
The expansion of female monasticism in the Central Middle Ages -- The old-fashioned way: Foundations in the tenth and eleventh centuries -- Nunneries in the Age of Change, circa 1080-circa 1170 -- Social and economic contexts in the eleventh and twelfth centuries -- The end of an era, circa 1170-circa 1215.
Includes bibliographical references (pages 215-233) and indexes.
Print version record.
Master record variable field(s) change: 072
Keywords: Convents -- Europe -- History; Monasticism and religious orders for women -- History -- Middle Ages, 600-1500.; Convents; Monasticism and religious orders for women -- Middle Ages; Europe; Nonnen; Vrouwenkloosters; RELIGION / Institutions & Organizations; RELIGION / Monasticism; History; Electronic books